Au nom de la lutte contre le changement climatique : le mécanisme pour un développement propre et ses travers - Moïse Tsayem Demaze (VertigO)
Established by the Kyoto protocol, the Clean Development Mechanism (CDM) allows developed countries to meet part of their commitments to reduce their greenhouse gases emissions (GHGE) by investing in projects carried out in developing countries. So, developed countries can receive certified emissions reduction corresponding to the volume of GHGE avoided or reduced in developing countries, and developing countries can claim a clean development. The use of CDM has drawn a lot of criticism and even controversies: unproven GHGE reduction, weak transfer of clean technologies, uneven geographical and sectoral distribution of projects, lack of sustainable development that CDM projects are expected to generate in developing countries, etc. This paper identifies and assesses these criticisms, using two newsletters reporting on the implementation of CDM projects in the world (Nouvelles Francophones du marché du carbone et du MDP, and Moniteur du MDP et de la Mise en Œuvre Conjointe). Criticisms identified and assessed were confronted with expert opinions of two International Non Governmental Organisations (INGO) specialised on the monitoring of the CDM implementation: CDM Watch and NOE 21. Interviews with managers of these INGO have permitted to evaluate the relevance of criticisms and the purpose and scope of the CDM. The results of this study raise questions about the effectiveness and the efficiency of the CDM, and about reforms proposed to ensure a better contribution of this mechanism to efforts to reduce GHGE.